Comparative study of transformational and transactional military and civilian leaders - Nader, Martín; Sánchez Santa-Bárbara, Emilio (Anales de Psicología / Annals of Psychology, 2010)
We present data corresponding to a study that had as first aim to determine if there are differences in values orientations of transforma-tional and transactional leaders while the second objective was to analyze if there are differences on values orientations between civilians and mili-tary officers. We have administered the Leadership Styles Questionnaire (Castro Solano, Nader & Casullo, 2004) and the Portrait Values Question-naire (Schwartz, 1992, 2001; Castro Solano & Nader, 2006) to 226 civilians and 138 military officers. Results showed that there are differences on values orientations between civilians and military. Military leaders were guided mostly by conservative values.